Valuing Options of Indonesia Composite Index: A Comparative Analysis of Binomial and Black-Scholes Models - Zahrah, Salsabila Az; Widyaningrum, Anisa Jannata; Rebika, Dinda Ayu Arsyil; Asshafwa, Ezzedine Humairo; Putri, Ivana Maharani (Universitas Brawijaya, 2025)
In this research, the valuation of the Indonesia Composite Index (IHSG) option prices is examined through the implementation and comparison of two common models: the Binomial model and the Black–Scholes model. The incubation of this work is the caustic drop of IHSG on March 18, 2025, which not only stopped trading on the Indonesia Stock Exchange but also sent shock waves through the market. We therefore investigate how increased volatility and anxiety in the market affect option pricing. Secondary data of IHSG closing prices from April 2024 to March 2025. From this data, they calculated daily logarithmic returns, estimated the volatility, and got the key parameters for options. The analysis focuses on at-the- money European call and put options with a maturity period of three months, which were valued before and after the trading halt. The results of the research show that the two methods are consistent, both models predict considerably higher option values as a result of a volatility increase from 27.13% to 31.28%. The evidence shows that greater market uncertainty raises the time value of call and put options, resulting in higher premiums regardless of the underlying asset’s movement. Furthermore, the strong agreement between the Binomial and Black–Scholes valuations confirms the robustness of both modeling approaches. These findings highlight the critical role of volatility in shaping option prices within emerging markets and emphasize the dual function of options as instruments for both risk hedging and speculative opportunities during periods of market stress, such as the IHSG trading halt in March 2025.